HUBUNGAN PROMOSI JABATAN DENGAN PRESTASI KERJA KARYAWAN PADA DIVISI PEMASARAN PT TRIBUN PEKANBARU - Ruliadi Krisna; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This reserach aims to determine the relationship promotion on employee achievement and analyze more deeply the relationship promotion on employee achievement marketing division of PT. Tribun Pekanbaru. Methods of data collection by questionnaire and interview. The concept of the studied variables there are 2 that independent variable is the indicator Promotion Position: Education, Experience, and Creative Initiative and the dependent variable is Job achievement indicators include: Responsibility, Discipline, Personality, Skills and Abilities. Measurements relationship promotion on employee achievement Marketing Division of PT. Tribun Pekanbaru by using a statistical test, which is a simple linear regression analysis, the coefficient of determination test, and t test. From the research, 73 respondents obtained results that promotion in the marketing division of PT. Tribun Pekanbaru is positioned properly or are in total score in 1332, the score interval (1244-1536), which means that the promotion consists of several indicators such as education, experience, and creative initiatives are already said to be good / agree. Based on calculations, the value of the regression coefficient for the value of X is 0.410 meaning that if the promotion increased by 1 unit then the work achievement parts marketing division of PT. Tribun Pekanbaru will increase by 0.410 units. From the regression equation above shows the regression coefficients of the independent variables that b is positive (+), where in this case the promotion variable (X) effect on work achievement. Significant influence on the interpretation promotion work has the effect of 38.2%. This means that 38.2% of work achievement is influenced by promotion.Keyword : Promotion, Work Achievement, Tribun Pekanbaru